2016
DOI: 10.4314/mmj.v28i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Uterine leiomyoma in a 19-year-old girl: Case report and literature review

Abstract: A previously healthy 19-year old female presented to the gynaecological clinic with gradual abdominal distension for six months, associated with progressive abdominal discomfort. There was no history of nausea, vomiting, weight loss, or anorexia. She reported no changes in bowel habits and denied genitourinary symptomatology. Menarche occurred at 14 years of age, and her menstrual periods had always been regular. She denied recent sexual activity and was not currently taking oral contraceptives. The remainder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…The slight difference observed is probably because of the differences in age grouping, but this suggests that women in this century are more likely to be involved in building a career. Results in this study does not agree with the case study by Ernest, Nwakalebela and Mpondo [19] that concluded that there is a rise in incidence of uterine fibroids in adolescents, this is because early menarche, exposure to exogenous oestrogen and other factors like obesity usually influence fibroid growth.…”
Section: Discussioncontrasting
confidence: 97%
“…The slight difference observed is probably because of the differences in age grouping, but this suggests that women in this century are more likely to be involved in building a career. Results in this study does not agree with the case study by Ernest, Nwakalebela and Mpondo [19] that concluded that there is a rise in incidence of uterine fibroids in adolescents, this is because early menarche, exposure to exogenous oestrogen and other factors like obesity usually influence fibroid growth.…”
Section: Discussioncontrasting
confidence: 97%
“…2023 May;12(5):1510-1512 early menarche, and exposure to exogenous oestrogen are common factors that affect fibroid development . 13 Because the majority of women with myomas are asymptomatic, the incidence of undiagnosed uterine fibroids is high. Women who are symptomatic are more likely to experience pelvic pain, infertility, pregnancy complications, and excessive uterine bleeding, which can lead to anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The values found in many countries on the African continent do not match those from the global perspective ( Figure 5 ), particularly those accepted as the prevalence values for Black women. The majority of the studies revealed fibroid occurrences of less than 30% ( Mutai et al, 2015 ; Ernest et al, 2016 ; Bineta et al, 2018 ; Hortence et al, 2021 ; Adawe et al, 2022 ). There may be severe undercoverage, as some of the available studies do not have access to many regions and are usually conducted in one hospital, resulting in a sampling bias.…”
Section: Non-hormonalmentioning
confidence: 99%